1972
DOI: 10.2136/sssaj1972.03615995003600030016x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Flow Rates of Salt and Water in Soil

Abstract: A hydrodynamic equation for the mixing of two miscible solutions in a porous media has been combined with the Gouy theory for ion distribution in soil pores in order to examine the effect of flow velocity and ion distribution in the pores on the breakthrough curves. The model considers zones of mobile and immobile solution in the porous media, and the extent these zones are affected by the total concentration of the solution and the pore water velocity.Miscible displacement experiments of 36Cl and 3H through P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…(56) using calculated values of rfrom Eq. This figure shows a comparison between calculated and experimental anion exclusion data (for a CaCl 2 system) as reported by: a) for kaolinitic and illitic clay soil; b) Thomas and Swoboda (1970) for a montmorillonitic clay soil; and c) Krupp et al (1972) for a montmorillonitic clay loam soil. 36.…”
Section: Modeling Of Anion Exclusionmentioning
confidence: 90%
“…(56) using calculated values of rfrom Eq. This figure shows a comparison between calculated and experimental anion exclusion data (for a CaCl 2 system) as reported by: a) for kaolinitic and illitic clay soil; b) Thomas and Swoboda (1970) for a montmorillonitic clay soil; and c) Krupp et al (1972) for a montmorillonitic clay loam soil. 36.…”
Section: Modeling Of Anion Exclusionmentioning
confidence: 90%
“…There have been several reported instances in which anion exclusion has been hypothesized to play a role in the flux of solutes though the vadose zone (Biggar and Nielsen 1962;Krupp et al 1972;Wierenga and van Genuchten 1989). Anion exclusion occurs when negatively charged species (solutes, colloids, microbes) are electrostatically repelled by negatively charged solid surfaces to travel at velocities in excess of those of the migrating fluids.…”
Section: Evidence Of Anion Exclusion During Vadose Zone Transportmentioning
confidence: 99%
“…This has been interpreted as temporary retention of tritium in an immobile water phase around clay particles (Kaufman and Orlob, 1956;Biggar and Nielsen, 1962;Krupp et al, 1972). Longer-term experiments have also shown that tritium may actually exchange with clay hydroxyls or become incorporated in the clay lattice, resulting in a more or less permanent fixation (Stewart, 1967;Rabinowitz et al, 1971).…”
Section: A Comparison Of Bomb-^^cl With Bomb-tritium In Various Hydromentioning
confidence: 99%